Synthesis and properties of 5-(((5-amino-1,3,4-thiadiazole-2-yl)thio)methyl)-4-phenyl-1,2,4-triazole-3-thione and its some S-derivatives - A. S. Hotsulia; S. O. Fedotov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Increased attention to thiadiazole and 1,2,4-triazole derivatives is determined by the extensive structural modification capabilities of heterocyclic system derivatives and their high pharmacological potential. Synthesis of new molecules containing, along with the 1,2,4-triazole moiety, thiadiazole is a promising trend in the field of biologically active substances.The purpose of this work was to study the reaction of nucleophilic substitution of 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione with haloalkanes and to establish the structure of the obtained compounds. Materials and methods. Thiosemicarbazide was used as the key starting reagent. As a result of the reaction of the starting material with carbon disulfide in dimethylformamide, a thione was obtained which was further reacted with the iso-propyl ester of the chloroethane acid. The resulting ester was used for further transformations using hydrazinolysis reaction, nucleophilic addition, and intramolecular alkaline heterocyclization. The alkylderivatives of the obtained 5-((5-amino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione were synthesized by reaction with bromoalkanes, in an alcohol medium with an equimolecular amount of alkali. The structure of the synthesized compounds was confirmed by modern physical-chemical methods of analysis: 1H NMR spectroscopy, IR spectrophotometry, and elemental analysis data. The individuality of substances was established by means of high-performance liquid chromatography.